FIELDS OF COMBAT : Understanding PTSD among Veterans of Iraq and Afghanistan - Finley, Erin P., 1977- (Culture and politics of health care work, 2011)
Both heartbreaking and hopeful, Fields of Combat tells the story of how American veterans and their families navigate the return home. Following a group of veterans and their personal stories of war, trauma, and recovery, Erin P. Finley illustrates the devastating impact PTSD can have on veterans and their families. Finley sensitively explores issues of substance abuse, failed relationships, domestic violence, and even suicide and also challenges popular ideas of PTSD as incurable and permanently debilitating.